Association Between Extraversion Personality With the Blood Pressure Level in Adolescents - Liang, Xiaohua; Hao, Guang; Xiao, Lun; Luo, Shunqing; Zhang, Guifang; Tang, Xian; Qu, Ping; Li, Rina (Frontiers in Cardiovascular Medicine, 2022)
Purpose The association between extraversion personality and high blood pressure (BP) has not been well-studied. This study aims to explore the association between extraversion personality and the BP level in a large sample of adolescents. Methods As an ongoing study, 5,246 children aged 6–9 years were recruited using a stratified cluster sampling method in 2014. The extraversion personality trait, assessed by the Eysenck personality questionnaire (EPQ, answered by adolescents) in 2019, was used in the main analysis. A total of 3,407 participants were eligible and included in this analysis. Results The EPQ extraversion score was negatively associated with a systolic BP, a diastolic BP, and mean arterial pressure (MAP) in a univariate analysis. After adjusting for other covariates, high extraversion score was negatively associated with systolic BP (β = −0.026; 95% CI = −0.047, −0.004; p = 0.002). There was an interaction between regions and the extraversion score on systolic BP (Pinteraction = 0.037). The stratified analysis showed that, in rural areas, the extraversion score was negatively associated with systolic BP (β = −0.050; 95% CI = −0.081, −0.016; p = 0.004). However, we did find an association between the extraversion score and systolic BP in urban areas (β = 0.000; 95% CI = −0.028, 0.028; p = 0.996). Similar results were observed for the extraversion assessed by parents. Conclusions We observed that extraversion personality was negatively associated with high BP in adolescents, especially for those who were living in rural areas. Our results suggested that a comprehensive intervention should be implemented to promote psychological health in adolescents.